Understanding of Media Literacy in Adolescents on the Use of Social Media in the Coastal Areas of Pematang Guntung Village - Fadhil Pahlevi Hidayat; Rudianto, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Social media users, especially adolescents, do not only occur in urban areas but also in coastal areas, especially in Pematang Putus village. The impact of globalization has made all levels of society, both urban and rural, exposed to the development of communication and information technology. Literacy is one of the initial and basic abilities that every individual must have in living life in the digital era. Therefore, the development of media literacy needs to be considered, by optimizing literacy learning, especially at the age of children and adolescents. The purpose of this study is to increase understanding and knowledge about social media for teenagers who are in the coastal area of Pematang Guntung Village by using media literacy based on the individual competence framework. The research method used is descriptive qualitative with phenomenological research type, determination of sources using purposive sampling model. The results showed that the media literacy skills of Pematang Guntung Village youth based on the individual competence framework of three indicators, namely technical skills, critical understanding, and communicative abilities were at the medium level. At the medium level, the literacy skills of Pematang Guntung Village's youth are at a level that is already fluent not only in using social media and the features in it but also having a critical attitude, knowing and assessing how information is obtained and needed by adolescents, and has the ability active communication through social media.